ANTECEDENTS OF QUALITY OF WORK LIFE DELIVERING ORGANISATIONAL CITIZENSHIP AND STRATEGIC PROFIT POSITION - Nivedhitha.K.S, Theerthaana.P (International Journal of Research Science and Management, 2016)
Organizations are increasingly indulging in quality of work life policies to actualize humanized work culture and improved retention rate. Many researchers have undergone intense discussions on various intrinsic and extrinsic antecedents of the quality of work life, yet the potentiality of team dynamics has not been given primal importance. This research is hoped to bridge the gap by considering dual questionnaires to analyze the requisites of diversified workforce (team leaders and team members). The research focused on 100 employees at Larsen and Toubro Ltd-LTM Business Unit, Chennai. Calculated χ2 is found to be 10.18(Tabulated χ2 = 5.991) proving unquestionable significant association between the job profile satisfaction and work stress. Positive Correlation between the training provided for team members and efficiency in diverse work groups with diverse tasks is found with R=0.91 and positive correlation between team’s cooperation and completion of team’s target is found with R= 0.72. These results confirm the substantial influence of team cooperation and the right job profile in inculcating a conducive quality of work life